Turnover Intention Analysis in Digitalization Era Within Covid-19 Pandemic Situation - Gunadi, Lie; Siahaan, Antonius; Adji, Ardi (Directorate of Academic Research and Community Services, 2021)
The phenomenon of the digitalization era has an impact on high employee turnover. On the other hand, the Covid-19 pandemic impacted a lockdown in many countries and regions which in turn, in many businesses and employees being affected (reducing costs, reducing working hours, and even laying off work relations). Taking a sample of various organizations in Indonesia, this study analyzed the factors that cause employee turnover intention (dependent variable) such as employee satisfaction (moderating variable), also remuneration & promotion, fringe benefit, working environment, and perceived external employment as independent variables. The research study was conducted based on 219 respondents who are in various industries. The results showed that working environment and fringe benefits have a positive impact to job satisfaction, job satisfaction has a negative impact to turnover intention and perceived alternate external employment has a positive impact to turnover intention inline with the predictions on the hypothesis. Meanwhile remuneration and perceived alternate external employment didn't have a significant impact on job satisfaction, as well as working environment, remuneration & promotion, and fringe benefits to turnover intention.